2008
DOI: 10.1071/wr07010
|View full text |Cite
|
Sign up to set email alerts
|

Regional faunal decline - reptile occurrence in fragmented rural landscapes of south-eastern Australia

Abstract: Many species of reptiles are sedentary and depend on ground-layer habitats, suggesting that they may be particularly vulnerable to landscape changes that result in isolation or degradation of native vegetation. We investigated patterns of reptile distribution and abundance in remnant woodland across the Victorian Riverina, south-eastern Australia, a bioregion highly modified (>90%) by clearing for agriculture. Reptiles were intensively surveyed by pitfall trapping and censuses at 60 sites, stratified to sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 33 publications
3
60
2
Order By: Relevance
“…Brown, Bennett, & Potts, 2008;Driscoll, 2004;Fischer, Fazey, Briese, & Lindenmayer, 2005;Fischer, Lindenmayer, & Cowling, 2003;Michael, Lunt, & Robinson, 2004), not least because so little is known about the impacts of many agricultural practices on the distribution and abundance of this diverse animal group, and the prospects that altered management, such as extensification, hold for it. Broadly, reptiles in these agri-landscapes are thought to be in decline Driscoll, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Brown, Bennett, & Potts, 2008;Driscoll, 2004;Fischer, Fazey, Briese, & Lindenmayer, 2005;Fischer, Lindenmayer, & Cowling, 2003;Michael, Lunt, & Robinson, 2004), not least because so little is known about the impacts of many agricultural practices on the distribution and abundance of this diverse animal group, and the prospects that altered management, such as extensification, hold for it. Broadly, reptiles in these agri-landscapes are thought to be in decline Driscoll, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Reptiles are an important element of the fauna in tropical forests worldwide, but their responses to tropical forest management are poorly understood (Alcala et al, 2004;Trainor and Woinarski, 1994;Gardner et al, 2007b;Cunningham et al, 2007). Reptile populations are especially sensitive to manipulations of the structure of vegetation communities (Vitt et al, 1998;Kavanagh and Stanton, 2005;Gardner et al, 2007a;Brown et al, 2008). Because plantation management strongly alters vegetation structure (McCullough, 1999), solar radiation levels, and environmental temperatures (Yirdaw and Luukkanen, 2004;Lemenih et al, 2004), the response of reptiles to plantations may be driven by their response to these environmental changes (JĂ€ ggi and Baur, 1999;Valentine, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss and fragmentation were identified as one of the main causes of extinction of woodland birds in Australia, related to poor dispersal to isolated patches, increasing nest predation, changes in habitat quality and resource availability, and increasing interspecific completion from aggressive bird species (Ford 2011). Brown et al (2008) found that reptiles in Victoria, Australia, had declined significantly with loss of habitat and changes in woodland structure, with declines in species richness even in remaining large patches. For howler monkeys in the Central and South American Neotropics, loss of habitat was more important than fragmentation on distribution and abundance, probably because howler monkeys are highly mobile and resistant to initial habitat disturbance (Arroyo-Rodriguez and Dias 2010).…”
Section: Drought-driven Change In Distribution and Numbers Wildlife Rmentioning
confidence: 99%